(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
This paper delves into the concept of selfless living through the lens of Karma Yoga, an ancient Indian philosophy that emphasizes the importance of selfless action. By integrating insights from psychology, neuroscience, and philosophy, we conduct a comprehensive examination of the benefits and mechanisms of selfless living, and how Karma Yoga provides a systematic approach to cultivating selflessness. Our analysis reveals that selfless living is associated with increased well-being, life satisfaction, and social connection, as well as reduced stress and anxiety. We also investigate the neural correlates of selfless living, including the activation of reward centres and the release of neurotransmitters such as oxytocin and dopamine. Additionally, we discuss the importance of self-awareness, self-regulation, and self-transcendence in Karma Yoga, and how these components contribute to the development of a selfless mindset. This paper contributes to a deeper understanding of the science behind selfless living and highlights the potential of Karma Yoga as a valuable framework for personal growth and social transformation. By exploring the intersection of Eastern philosophy and Western science, we aim to provide a holistic understanding of selfless living and its benefits for individuals and society. Our research has implications for the development of interventions and programs aimed at promoting selfless living, and highlights the need for further research in this area. Furthermore, we discuss the potential applications of Karma Yoga in fields such as education, healthcare, and community development. Ultimately, this research seeks to inspire a greater sense of purpose, meaning, and connection in individuals, and to promote a more compassionate and harmonious world.